Ensuring Straight-Line Motion of the Hexacopter in Case of One Engine Failure - Nabadova, Gulush; Sabziev, Elkhan (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
It has been observed that the number of accidents due to technical malfunctions in the engines of drone-type unmanned aerial vehicles during mass production has risen significantly. When one of the aircraft’s engines fails, the remaining engines must compensate to maintain the mission. This research focuses on the challenges of controlling hexacopter-type unmanned aerial vehicles with six engines in the event of a single engine failure. The paper outlines the mathematical principles for managing the hexacopter’s engines so that it can continue operating as it did before the malfunction. The findings indicate that the limited power of the remaining engines may not be enough to sustain the mission without adjustments.